Nanotechnology in Medicine: Physics-Based Approaches for Targeted Drug Delivery and Early Detection - Khalid, Zaid Luay; Rasheed, Narmeen Ahmad; Mustafa Ali, Saraa Luqman; Hamza, Ahmed Ali Marza; Salem, Hajar Hameed (American Journal of Botany and Bioengineering, 2025)
The field of cancer nanomedicine has begun to see success in clinical applications, but has yet to reach its full potential. There is mounting evidence in preclinical studies that effective encapsulation of small-molecule drugs, nucleic acids, or other modalities may be capable of mediating comprehensive cancer management, or even a potential cure. However, this field is limited by the difficulty in designing and fabricating systems for complete treatment. The pharmaceutical industry is intensely focused on the rapid improvement of delivery systems that make use of physics-based approaches to improve drug biodistribution. Recently, many have used such frameworks to engineer nano-scale systems or to optimize existing NP libraries. Resistance to this new paradigm of cancer treatment comes partially due to the immense mechanistic and pharmacokinetic barriers that inherently exist within the body. There is a limited range of successful achievements in nanoformulation treatment, but the potential success has spurred an intensive interdisciplinary interest in nanomedicine. An explicit need exists for more comprehensive theoretical and experimental methods to complement preexisting NP design techniques. A broad, but practical overview survey of the modeling frameworks can be used to streamline treatment design processes. With increased utility for computational and analytical tools, the paradigm of physics-based approaches that overcome barriers to treatment can be more effective.